2012
DOI: 10.1097/rli.0b013e31824c86a3
|View full text |Cite
|
Sign up to set email alerts
|

Metal Artifact Reduction by Dual-Energy Computed Tomography Using Energetic Extrapolation

Abstract: Sn140/100 kVp with a tube current ratio of 3:1, a collimation of 32 × 0.6 mm, and extrapolated energies of 105 to 120 keV are optimal parameters for a dedicated DSCT protocol that effectively reduces metal artifacts by energetic extrapolation. The protocol effectively reduces metal artifacts in all types of metal implants. The optimized reconstructions yielded relevant additional findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 26 publications
6
107
4
5
Order By: Relevance
“…A DECT protocol optimization study by Meinel et al 6 showed that optimal MAR was seen when using a monoenergetic level of between 105 and 120 keV. Recommendations from application specialists from the different CT scanner vendors and from radiologists in the hospital's clinic reasonably coincided with this conclusion.…”
Section: Phantom Imagingmentioning
confidence: 88%
See 2 more Smart Citations
“…A DECT protocol optimization study by Meinel et al 6 showed that optimal MAR was seen when using a monoenergetic level of between 105 and 120 keV. Recommendations from application specialists from the different CT scanner vendors and from radiologists in the hospital's clinic reasonably coincided with this conclusion.…”
Section: Phantom Imagingmentioning
confidence: 88%
“…This application makes it possible to obtain images as though they had been acquired with a monoenergetic high-energy beam, which would lead to reduction of metal artefacts caused by beam hardening. [5][6][7][8][9] In addition to monoenergetic reconstructions in DECT, dedicated MAR algorithms have become available for clinical practice in the past couple of years. MAR algorithms in both single-energy CT imaging [10][11][12][13][14] and DECT imaging 8,9 have been shown to reduce metal artefacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,14 However, the effectiveness of artifact reduction by using monoenergetic imaging appears to be dependent on implant material and size. 7,9,12,13 Our work used a method for metal artifact reduction that can be employed using conventional single-energy CT acquisition with thresholds and other settings potentially altered to adjust for different types and location of metal implants. Others have previously described a 1D linear interpolation to improve CT sinogram data, 15,16 but such approaches have not been put into clinical practice until recently, primarily due to the high computational time requirements.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 On CT, beam-hardening and photon starvation artifacts from metallic fusion hardware frequently compromise visualization of critical anatomic structures and pathologic findings, particularly in the ROI near implanted hardware. Recent publications have presented several postprocessing methods for decreasing the severity of metal implant artifacts in CT. [7][8][9][10][11] These works describe unique challenges to minimizing metal-related artifacts in different body regions due to differences in local anatomy and in implant composition. 12 However, only a few of these works focused on the unique challenges of the postoperative spine, 12,13 and none assessed visualization of the critical anatomic structures that the neuroradiologist must evaluate in the postoperative setting.…”
mentioning
confidence: 99%